Associations between internet addiction, grit, perceived stress and academic performance in medical students - Aziz, Nusrat; Fatima Khan, Sheema; Qatoon, Shaik Simra; Siddiqui, Maryam; Zainab,; Fatima Khan, Shams (International Journal of Research in Medical Sciences, 2024)
Background: Medical students require high academic performance and dedicated training with focus, optimism and a growth mindset. Our study aims to analyse the associations between internet addiction, Grit, perceived stress with academic performance in 1st year medical students. Methods: First year female medical students with convenience sampling of 100 had been asked to self-administer the Young’s internet addiction test, Cohen’s perceived stress scale and grit scale by Duckworth after giving informed consent. Association between the above parameters and their effect on academic performance was studied and analysed. Results: Prevalence of internet addiction in medical students was as high as 90% including 20% moderate and 70% mild internet addiction. 31% of students showed high perceptive stress, 59% moderate and 10% low stress. The mean grit estimated was 3.04 (SD-0.65062). Student’s perceptive stress was positively correlated with internet addiction. Higher internet addiction score showed lesser academic grades. Students with more grit showed less internet addiction and better academic performance having a significant positive correlation. Students with moderate stress showed better academic grades than low or high stressed students. Conclusions: In light of the above findings, it is important that once the students enter medical school, they must be given study tips and guidance to develop mindset for more grit, stress management and made aware of ill effects of spending more hours on internet for purposes other than learning. This will help them to concentrate better strive towards attainment of their long-term goals, avoid overstress and achieve higher academic grades.